Optimizing Service Quality Through a People, Process, and Technology Approach for Freelance Tour Guides (Case Study of Timotravel) - Timotius Herman; Achmad Ghazali (International Journal of Science and Environment (IJSE), 2025)
This study examines the factors that contribute to inconsistent service quality among freelance tour guides at Timotravel, a newly established Indonesian SME operating in the outbound travel industry. As the company relies heavily on freelancers due to financial constraints and fluctuating demand, variations in guide competence, destination knowledge, time management, and professionalism have resulted in lower customer satisfaction and reputational risks. Using a qualitative case study approach, data were collected through semi-structured interviews with customers and freelance tour guides who participated in recent tours. The research applies the People, Process, and Technology (PPT) framework combined with Business Process Management (BPM) to analyze root causes and identify improvement pathways. Findings reveal three major sources of service variability: (1) people-related issues, including insufficient soft skills, limited destination knowledge, and lack of standardized competency requirements; (2) process-related weaknesses, such as incomplete or non-contextual SOPs that fail to guide real-time decision-making; and (3) technology-related gaps, including the absence of integrated systems for briefing, feedback collection, and knowledge sharing. The analysis highlights that inconsistencies are not solely the result of individual shortcomings but stem from systemic misalignment within Timotravel’s service design. Based on these findings, this research proposes an integrated improvement model consisting of enhanced competency training, redesigned SOPs aligned with BPM Level 1–3 process mapping, and the implementation of basic technological support tools such as CRM-driven feedback tracking and digital guide briefings. These recommendations are expected to improve service consistency, optimize operational performance, and strengthen customer satisfaction. The study contributes to service science literature by demonstrating how a PPT-driven approach can be applied to SMEs with limited resources to standardize service delivery while leveraging freelance-based human resources.